EEDUKASI PEMBUDIDAYAAN DAN PEMANFAATAN TANAMAN HERBAL KELUARGA (TOGA) DI KAMPUNG MALAWOR - Irfandi Rahman; Julya Finsilya Ratulohoren; Prisilya Prety Ruhukail; Miranda Taborat; Eden Nasrani Manubuy; Trysa Ade Wahyuningtias; Susanti Debora Kadiwaru; Marcelino Brevian Pitres Sanggono; Irham Marselino (Politeknik Negeri Sriwijaya, 2022)
Family medicinal plants are types of plants that can be cultivated alone and can be useful for medicine and can also be aesthetic garden plants. Family medicinal plants can fulfill preventive (disease prevention), promotive (health promotion), curative (disease healing), and rahabilitative (health restoration) efforts. Malawor village is located in a strategic location, where the large village hall yard can be used as a family garden for herbal medicinal plants. The purpose of education and training is to cultivate herbal plants and utilize family herbal medicinal plants by the people of Kampung Malawor. and after education and training the community has understood how to use and cultivate family herbal medicinal plants. The conclusion with education and training has been to increase understanding and knowledge in helping to cultivate family herbal medicines in Malawor Village.